COMMUNITY LEGAL WORKERS IN ONTARIO: A PARALEGAL CASE STUDY - Frederick H Zemans (Obiter, 2022)
This article examines the history of community legal workers in Ontario, within the context of the community legal clinic movement that began in Toronto, in the early seventies. Tracing the emergence and development of community legal clinics and how their role has changed, the author directly connects the changes in the legislation, as well as the administrative changes in clinic governance, to the shifting role of the CLW’s within Ontario’s community legal clinics. The article identifies the shift in the CLW’s role from one largely of community outreach and education addressing systemic problems in access to justice, to one where, increasingly, CLWs are principally expected to address the growing demand for casework and related tasks. Ontario’s experience illustrates how funding formulas and models of governance directly impact not only on the way in which legal clinics connect to their community, but also how they contribute to social change. The significance of the innovative and strategic use of community legal workers is underlined by their continued importance within Ontario’s growing community legal clinic system.